Digital fiber length determination for injection molded glass fiber reinforced composite materials - Andreas Grießer; Nelly Nunheim; Oliver Rimmel; Erik Glatt; Anne Blumer; Hans Hagen; Andreas Wiegmann (e-Journal of Nondestructive Testing)
Fibrous materials are essential in industries such as lightweight automotive materials [1] [2], filtration [3], and hygiene products [4]. The properties of these materials depend on microstructural geometric statistics, making the analysis of individual fibers a powerful tool in material engineering. Fiber length, for example, is a fundamental parameter influencing material properties in composites and nonwovens. Traditional methods for determining fiber length are labor-intensive, prone to user bias, and time-consuming. In contrast, CT-scan-based approaches offer a novel, non-destructive, and reproducible method to assess fiber length distribution. These digital techniques enable the easy analysis of freshly manufactured samples and their re-examination after use to investigate material aging, including changes in fiber length, the matrix, or other components. In this work, we present our method to measure fiber length in micro-CT-scans and compare it to an established experimental method.